Polishing of AlN/sapphire substrates obtained by thermochemical nitridation of sapphire - Vovk, E.A.; Budnikov, A.T.; Nizhankovskyi, S.V.; Kryvonogov, S.I.; Krukhmalev, A.A.; Dobrotvorskaya, M.V. (Functional Materials, 2013)
Physicochemical conditions and polishing suspension composition were established for polishing of AlN/sapphire templates obtained by thermochemical nitridation of sapphire. The use of the polishing suspension based on aerosil and KOH with pH 10.3 allowed to prepare the surface with a roughness Ra up to 1 nm. The morphology and element composition of AlN/sapphire surface at layer-by-layer removal of the nitridated layer were studied by the methods of atomic force microscopy and X-ray photoelectronic spectroscopy.